BEI for Creative Industry In Indonesia - Gancar Premananto; Sri Hartini; Jovi Sulistyawan (Universitas Hayam Wuruk Perbanas, 2018)
The purpose of this research is to provide a description of the implementation of ethics business in creative industry in Indonesia. This study focuses on understanding the Business Ethics Index (BEI) in Indonesia, especially for the creative industry in millennial generation perception. This study uses survey method with 136 respondents who are millennial generation. In addition, this research also uses 3 subsectors, namely culinary industry, art industry, and showbiz industry. Sampling is done by accidental sampling. The measurement of BEI is done using 4 dimensions, namely